Prevalence of gastrointestinal disorders in adults with common variable immunodeficiency at Specialty Hospital Dr. Bernardo Sepulveda - Elda Victoria Rodríguez-Negrete (Revista Alergia México, 2015)
Background: The common variable immunodeficiency (CVID) shows a variable incidence, from 1:15,000 to 1:117,000, whitout gender predominance. The incidence of gastrointestinal manifestations in these patients ranges from 20-60%, and these may be the first and only clinical mafifestation of CVID, while other patients develop gastrointestinal complicatons during the course of it.